Significados de família para adolescentes em liberdade assistida - Araújo, Emília de Rodat Peixoto de (2007)
Guided by the social-historical perspective, this research aimed to understand how the adolescents in Assisted Freedom measure have meaning the family institution. The Pastoral Minor, located in the city of Natal, was chosen as space of investigation, whose social-educative program is the source of our concerns about the attendance of adolescents in conflict with law. The corpus was accomplished, mainly, through the individual semi- structured interview with four adolescents and seven of their relatives that participated of the research. We use another instruments to constitute the corpus, like the documental research of the technical reports on the participants of program files, and the registered notes in the field diary. As resource to data treatment, we use the Thematic Content Analysis. The data discussion was focused on the three thematic units that emerged: Family, Social-Educational Measure, Family and Social-Educational Measure. On the adolescents perspective, the family configures as a group based on the existence of affective bonds. Despite of the vulnerability of their familiar reality and their wish for freedom with their peers, the affective bonds revealed it as being important in their lives. This study, glimpse possibilities to contribute for the construction of public politics and attendance programs, that can be closer of the social-familiar reality of the adolescents who are in conflict with the law and, in this case, to promote their access to the statute of subjects of rights